ҚОРАҚАЛПОҚ ТИЛШУНОСЛИГИДА ФРАЗЕОЛОГИЗМЛАРНИНГ ЎРГАНИЛИШИ - Хайтбаев, О.; Кудьярова, Ш. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of issues of phraseology in Karakalpak linguistics. Issues of phraseology remain in the centre of attention of many linguists and they take an honorable place in their research works. The author of the article also studies the synonymy, homonymy and antonymy of phraseological units.